Evaluation of co-pyrolysis petrochemical wastewater sludge with lignite in a thermogravimetric analyzer and a packed-bed reactor: Pyrolysis characteristics, kinetics, and products analysis. (December 2016) - Mu, Lin; Chen, Jianbiao; Yao, Pikai; Zhou, Dapeng; Zhao, Liang; Yin, Hongchao
Highlights: Co-pyrolysis of sludge and lignite was studied by TGA and packed-bed reactor. Evaluation of pyrolysis kinetics was performed by integral Coats–Redfern method. Synergetic effects during fast pyrolysis promoted the evolution of volatiles. Functional groups for chars and volatiles, and gas compositions were analyzed. Abstract: Co-pyrolysis characteristics of petrochemical wastewater sludge and Huolinhe lignite were investigated using thermogravimetric analyzer and packed-bed reactor coupled with Fourier transform infrared spectrometer and gas chromatography. The pyrolysis characteristics of the blends at various sludge blending ratios were compared with those of the individual materials. Thermogravimetric experiments showed that the interactions between the blends were beneficial to generate more residues. In packed-bed reactor, synergetic effects promoted the release of gas products and left less liquid and solid products than those calculated by additive manner. Fourier transform infrared spectrometer analysis showed that main functional groups in chars gradually disappeared with pyrolysis temperatures increasing, and H2 O, CH4, CO, and CO2 appeared in volatiles during pyrolysis. Gas compositions analysis indicated that, the yields of H2 and CO clearly increased as the pyrolysis temperature and sludge blending ratio increasing, while the changes of CH4 and CO2 yields were relatively complex.